PEMBELAJARAN MODEL JIGSAW PADA MATA KULIAH BAHASA INDONESIA DI POLITEKNIK LP3I MAKASSAR - Salam, Husni Bt; Basri, Basri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Indonesian language courses are compulsory subjects in every tertiary institution so a learning model is needed. The purpose of this study is to describe the Lesson Studybased cooperative learning model in the Indonesian language course at the Polytechnic LP3I Makassar. This research was conducted in 2 cycles. The subjects in this study were 22 students of Business Administration class. The research instrument consisted of the Lesson Study feasibility study instrument sheet, the observation sheet of problem solving skills assessment and the cognitive assessment assessment sheet. The results of the study used a Lesson Study based jigsaw method of 90%. The application of the Jigsaw model based on Lesson Study was able to improvestudent collaborative skills by 8.26% and cognitive learning outcomes by 1.56% from cycle I to cycle II. The conclusion of this research is a strategy using the Jigsaw model based on Lesson Study can improve the collaborative skills and cognitive learning outcomes of each student.